2018
DOI: 10.2478/macvetrev-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning of Dogs in the Republic of Macedonia- Pathomorphological Changes and the Impact on Animal Welfare

Abstract: The illegal poisoning of dogs and other domestic and wild animals presents a worldwide problem causing animal suffering and R. Macedonia is not an exeption. The goal of this study is to make a comparison of the results from the histopathological examination conducted among poisoned dogs in the Republic of Macedonia. Morphological and histopathological changes in poisoned dogs were investigated for a period of 10 years. The examination was performed on 31 dogs, 13 of which were home kept, 7 were street dogs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In another study performed in rats, degenerative changes were observed in the brains of the methomyl-administered groups (10 mg/ kg, 2 mg/kg) compared to the control groups [14] . In a study of dog poisoning cases in Macedonia in 2007-2017, it was reported that the most important necropsy findings in methomyl poisoning events were inflammatory changes in the gastrointestinal tract and histopathologically the most affected organs were the kidney, stomach, intestine, and lung [15] .…”
Section: Discussionmentioning
confidence: 99%
“…In another study performed in rats, degenerative changes were observed in the brains of the methomyl-administered groups (10 mg/ kg, 2 mg/kg) compared to the control groups [14] . In a study of dog poisoning cases in Macedonia in 2007-2017, it was reported that the most important necropsy findings in methomyl poisoning events were inflammatory changes in the gastrointestinal tract and histopathologically the most affected organs were the kidney, stomach, intestine, and lung [15] .…”
Section: Discussionmentioning
confidence: 99%